2009
DOI: 10.1002/hbm.20529
|View full text |Cite
|
Sign up to set email alerts
|

Language and music: Differential hemispheric dominance in detecting unexpected errors in the lyrics and melody of memorized songs

Abstract: Using magnetoencephalography (MEG), we report here the hemispheric dominance of the auditory cortex that is selectively modulated by unexpected errors in the lyrics and melody of songs (lyrics and melody deviants), thereby elucidating under which conditions the lateralization of auditory processing changes. In experiment 1 using familiar songs, we found that the dipole strength of responses to the lyrics deviants was left-dominant at 140 ms (M140), whereas that of responses to the melody deviants was rightdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
1
10
0
1
Order By: Relevance
“…However, the melodies that we utilized are commonly associated with lyrics (e.g. "Happy Birthday To You"), the processing of which has shown to be related to left hemispheric top-down mechanisms for highly familiar songs (Yasui et al 2009). It is plausible that the extratemporal activations observed during melody perception in the inferior frontal gyrus were due to lexicosemantic access in an effort to match lyrics to the presented melody (Platel et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, the melodies that we utilized are commonly associated with lyrics (e.g. "Happy Birthday To You"), the processing of which has shown to be related to left hemispheric top-down mechanisms for highly familiar songs (Yasui et al 2009). It is plausible that the extratemporal activations observed during melody perception in the inferior frontal gyrus were due to lexicosemantic access in an effort to match lyrics to the presented melody (Platel et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The easier access was possibly because the semantic features of related targets had already been pre-activated when the subjects processed the final word in the lyrics, suggesting that lyrics processing was automatically engaged even though that was not necessary in completing the required experimental task. As noted in Introduction, earlier literature on song perception usually presented songs sung/synthesized a cappella Bonnel et al, 2001;Sammler et al, 2010;Yasui et al, 2009) and directed subjects' attention to the lyrics or melody Bonnel et al, 2001;Crowder et al, 1990;Gordon et al, 2010;H ebert & Peretz, 2001;Poulin-Charronnat et al, 2005;Serafine et al, 1984). To make our experiment more ecologically valid, we used pop songs as experimental materials because people usually listen to them in a natural setting (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…What effect would song familiarity bring to listeners in song perception? An MEG study found that familiar songs exerted a top down effect on song perception such that the brain response to melodic deviants appeared as early as 130 ms in the right hemisphere and that to linguistic deviants occurred as early as 140 ms in the left hemisphere (Yasui, Kaga, & Sakai, 2009). As impressively rapid as it may be, fast recognition may simply be a by-product effect that familiar songs bring to listeners in everyday life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Π’ Ρ€Π°Π±ΠΎΡ‚Π΅ Π’. Ясуи, К. Кага, К. Π‘Π°ΠΊΠ°ΠΈ [21] ΡΡ€Π°Π²Π½ΠΈΠ²Π°ΡŽΡ‚ΡΡ ΠΌΠ΅Ρ…Π°Π½ΠΈΠ·ΠΌΡ‹ Ρ€Π°Π±ΠΎΡ‚Ρ‹ ΠΌΠΎΠ·-Π³Π° со словами ΠΈ ΠΌΡƒΠ·Ρ‹ΠΊΠΎΠΉ пСсСн. Авторы приходят ΠΊ Π²Ρ‹Π²ΠΎΠ΄Π°ΠΌ ΠΎ Ρ‚ΠΎΠΌ, Ρ‡Ρ‚ΠΎ ошибки Π² тСкстС ΠΊΠΎΠ½-Ρ‚Ρ€ΠΎΠ»ΠΈΡ€ΡƒΠ΅Ρ‚ слуховая ΠΊΠΎΡ€Π° ΠΈ Π² словах, ΠΈ Π² ΠΌΠ΅Π»ΠΎΠ΄ΠΈΠΈ, ΠΏΡ€ΠΈΡ‡Π΅ΠΌ Ρƒ ΠΏΡ€Π°Π²ΠΎΠΏΠΎΠ»ΡƒΡˆΠ°Ρ€Π½Ρ‹Ρ… Ρ€Π°ΡΠΏΠΎΠ·Π½Π°ΡŽΡ‚ΡΡ быстрСС ошибки Π² ΠΌΠ΅Π»ΠΎΠ΄ΠΈΠΈ, Π° Ρƒ Π»Π΅Π²ΠΎΠΏΠΎΠ»ΡƒΡˆΠ°Ρ€Π½Ρ‹Ρ… -Π² тСкстС.…”
unclassified